Comparative Analysis of Bottom Set Long Line and Boat Seine Fishing Effort Productivity In Juwana, Pati Regency - Setyorini Setyorini; Agus Suherman; Imam Triarso (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2009)
Bottom set long line and Boat seine are the divece which more used by fisherman at Juwana - Pati. This research is used for learn and comparison of productivity rate and many factors and profit rate rate of catch applied of Bottom set long line and Boat seine in Juwana - Pati. This research is used descriptive method. The output of this research is the productivity average per unit of Bottom set long line is 39,09 ton/unit/trip. Productivity per ABK is 0,89 ton/people/trip and the productivity average per trip is 12,27 ton/trip. The productivity average of boat seine is 260,10 ton/unit/trip. Productivity per ABK is 0,92 ton/people/trip and productivity average per trip is 12,60 ton/trip. Factor which influence the fishery product of Bottom set long line and Boat seine is the operasional value.F test analysis is known that all free variable can influence unfree variable significantly, which coefisien rate of determination (R2=R square) for bottom set long line is 96,6% and coefisien rate 97,7% for boat seine with the fault probability < 0,05 or Fhit> T tab Key word : Bottom set long line, Boat seine, Productivity, Pati